Taxonomic and functional groups of phytoplankton in the Northern Gulf of Lake Tana, Ethiopia - Flipos Engdaw; Demeke Kifle; Tadesse Fetahi (Journal of Freshwater Ecology)
Water quality of Lake Tana has been deteriorating due to nutrient enrichment associated with various anthropogenic stressors including domestic and industrial effluents, and agricultural runoff. Changes in the ecological health of a lake are better understood by studying the community structure of phytoplankton as they react quickly to environmental changes. Human-induced stressors can lead to changes in the taxonomic composition and Reynolds functional groups (RFGs) of phytoplankton resulting in biodiversity impoverishment. RFGs are more effective in detecting stressor-induced alterations in phytoplankton compared to taxonomy-based assemblages as the former reflect common adaptive or functional traits. Information on RFGs of phytoplankton in the northern gulf of Lake Tana, Ethiopia, is however non-existent. Therefore, this study aimed to assess the spatio-temporal changes in phytoplankton community structure and identify the variables influencing the dynamics of RFGs in the lake. Samples were collected from five sampling sites between May 2023 and April 2024. A total of 113 phytoplankton species belonging to six taxonomic groups and 11 RFGs were identified. The predominant RFGs which collectively accounted for 97% of the total phytoplankton abundance were M, B, N, D, Lo, P and S2. Other RFGs, such as J and X1–X3, constituted 2.4% and 0.8% of the total abundance, respectively. Redundancy analysis indicated significant association of RFGs with electrical conductivity, pH, turbidity and some algal growth limiting nutrients. This suggests that both biotic and anthropogenic stressors have a substantial impact on RFGs. Therefore, continuous monitoring is essential to prevent future ecological imbalances in the lake.